2023
DOI: 10.1111/jtxs.12739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial replacement of unwashed Antarctic krill surimi by Litopenaeus vannamei surimi on the heat‐induced gelling and three‐dimensional‐printing properties

Abstract: There is an emerging consumption of the Antarctic krill (AK) muscle‐based food due to its excellent nutritional value and enormous biomass storage capacity. However, the coarse texture of the muscle and the weak gelling properties of AK protein impede its expansion in surimi‐based products. This investigation successfully prepared heat‐induced gels of AK surimi with desirable textural properties by including Litopenaeus vannamei in varying proportions. Higher concentrations of L. vannamei resulted in improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…LF‐NMR is appropriate for evaluation of the effects of heating and freezing treatments on 3D/4D printed foods, as Figure 4c shows, LF‐NMR can be used to illuminate the linkage among the obstruction of water migration with the increase of mechanical strength within 3D printed surimi gel (C. Wang et al., 2023). In addition, T 2 has been combined with WHC to elucidate the impact of water distribution on the level of amalgamation among bound water, free water, and other constituents such as protein and starch (M. Li et al., 2023; Shang et al., 2023).…”
Section: Characteristics Of 3d/4d Printed Srfsmentioning
confidence: 99%
“…LF‐NMR is appropriate for evaluation of the effects of heating and freezing treatments on 3D/4D printed foods, as Figure 4c shows, LF‐NMR can be used to illuminate the linkage among the obstruction of water migration with the increase of mechanical strength within 3D printed surimi gel (C. Wang et al., 2023). In addition, T 2 has been combined with WHC to elucidate the impact of water distribution on the level of amalgamation among bound water, free water, and other constituents such as protein and starch (M. Li et al., 2023; Shang et al., 2023).…”
Section: Characteristics Of 3d/4d Printed Srfsmentioning
confidence: 99%
“…This phenomenon occurs because salt dissolves salt-soluble thick and thin myofilaments, allowing myosin and actin to absorb water and assemble into an actomyosin gel. The expansion of the actin structure increases the stickiness, hardness,and adhesion of surimi. , In recent years, it has been reported that common shrimps such as Litopenaeus vannamei have been used as raw materials to prepare commercially marketable shrimp paste products. , However, the surimi products formed by shellfish, another important organism in the ocean that is also high in protein, have not yet been widely available.…”
Section: Relationships Between Actin and Food Qualitymentioning
confidence: 99%
“…70,71 In recent years, it has been reported that common shrimps such as Litopenaeus vannamei have been used as raw materials to prepare commercially marketable shrimp paste products. 72,73 However, the surimi products formed by shellfish, another important organism in the ocean that is also high in protein,…”
Section: Relationships Between Actin and Food Qualitymentioning
confidence: 99%
“…Surimi is a typical salt-soluble myofibrillar protein concentrate and can be produced from low-value freshwater fish, such as silver carp (Ding et al, 2022). However, silver carp surimi has undesired flavour, rough gel and whiteness through several rinsing steps removed fish oil (Luo et al, 2020), which is necessary to add exogenous additives, such as plant protein, starch and edible oil to control its quality (Yang, Meng, et al (2022); You et al, 2022;Shang et al, 2023). The addition of edible oil is an effective way to improve the texture and colour of surimi as well as enhance the nutritional and flavour value of surimi products (Yu, Xiao, et al, 2022;Pei et al, 2023).…”
Section: Introductionmentioning
confidence: 99%